EVALUASI KEKUATAN TANAH DASAR BERDASARKAN UJI CALIFORNIA BEARING RATIO PADA SUATU RENCANA KAWASAN WISATA - Simanjuntak, Samuel; Nugraha, Andrias Suhendra (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
Subgrade strength is a crucial factor in pavement design for areas subjected to static and dynamic traffic loads. This research aims to evaluate the subgrade's bearing capacity at a planned tourism area in Lembang, West Java. The evaluation was conducted using the field CBR test method in accordance with ASTM D 4429 and SNI 1738:2011. Data collection was carried out at 12 scattered areas, covering a total of 89 representative test points. The results show that the actual CBR values varied significantly with average values at each test area ranging from 4.35% to 6.45%. Although all values met the minimum design requirement (>2%), most of the subgrade conditions were classified as